PRAKTIK CORPORATE GOVERNANCE DAN RISK DISCLOSURE STUDI EMPIRIS DI INDUSTRI PERBANKAN INDONESIA - Rudi Zulfikar, Djoko Suhardjanto (Jurnal Akuntansi, 2013)
The purpose of this research is to examine the role of Corporate Governance practice to risk disclosure in Industry of perbankan Indonesia.  Corporate Governance practice (CG) was measured by: proportion of board of directors independent member, proportion of board of directors members eduaction background, the number of meeting of board of directors, the proportion of board of directors member, proportion of risk monitoring committe independent member, the number of meeting of risk monitoring committe. The sample of this study was 62 banks listed  in the Indonesian Stock Exchange within the year of 2010 and 2011. The data are drawn from the annual report in the website of the companies. This research find that proportion of board of directors independent member, the and the number of meeting of risk monitoring committee are significant to risk  disclosure. . This result indicates that the level of  risk disclosure is depend to board of directors independent member and the number of meeting of risk monitoring committee.